Death ligand/receptor-independent caspase activation mediates drug-induced cytotoxic cell death in human malignant glioma cells - Glaser, Tamara; Krammer, Peter H. (Oncogene, 1999)
Death ligand/receptor interactions and caspase activation mediate drug-induced apoptosis in certain cancer cells. The molecular mechanisms responsible for the chemoresistance of human malignant gliomas are largely unknown. Here, we report that malignant glioma cells co-express CD95 and CD95L without undergoing suicidal or fratricidal apoptosis. Glioma cells do not commit CD95/CD95L-dependent suicide or fratricide even when RNA and protein synthesis are inhibited. This is because ectopic expression of the viral caspase inhibitor, crm-A, or exposure to a neutralizing CD95L antibody, block apoptosis induced by exogenous CD95L but not cell death induced by cytotoxic concentrations of inhibitors of RNA and protein synthesis. Although some cytotoxic drugs enhance the expression of CD95 or CD95L, crm-A fails to block drug-induced cytotoxic and clonogenic cell death, suggesting that the drug-induced changes in CD95 and CD95L expression are epiphenomenal. There is also no difference in drug-induced apoptosis between crm-A-transfected and control cells as assessed by electron microscopy, in situ DNA end labeling and DNA fragmentation. Further, glioma cells selected for resistance to CD95L do not acquire cross-resistance to chemotherapy. However, the broad spectrum caspase inhibitor, ZVAD-fmk, inhibits drug-induced cytotoxic cell death, suggesting a role of crm-A-insensitive caspases in drug-induced apoptosis of glioma cells. Thus, drug resistance of malignant glioma cells may involve deficiencies in two interrelated pathways that mediate death in order tumor cell types: (i) death ligand/receptor signalling; and (ii) caspase activation.
Gesehen am 23.04.2021